Present status of Fish biodiversity and factor affecting the Biodiversity of Bengali river in Gaibandha of Bangladesh: Status and Threats to Fish Biodiversity in the Bangali River - Siddque, Md Abu Bacckur; Islam, Md Jahidul; Kunda, Mrityunjoy; Uddin, Md Moslem (Journal of the Sylhet Agricultural University, 2026)
Fish diversity in Bangladesh’s major rivers is declining, but the lack of comprehensive research means their current status remains largely undocumented. This study addressed the issue in the Bangali River using a pre-tested questionnaire, direct catch assessments, and interviews with fishers, traders, locals, and the upazila fisheries officer. A total of 49 fish and prawn species were documented, belonging to 10 orders and 17 families. Cypriniformes, Siluriformes, and Perciformes emerged as the most prominent orders, accounting for 40.81%, 22.45%, and 14.28% of the total fish population in the Bangali River, respectively. Among the families, Cyprinidae (38.78%) was identified as the most dominant, followed by Bagridae (10.20%), Cobitidae, and Ambassidae (6.12%). These results demonstrate that the Bangali River is a highly valuable inland open waterbody, potentially serving as a vital fishery and gene bank. Therefore, it is imperative to implement conservation measures to safeguard this invaluable resource. Manmade activities like overfishing, use of pesticides, operation of illegal gear and natural causes such as climate change and drought are accelerating biodiversity degradation in the Bangali River. Furthermore, adopting ecosystem-based fisheries management strategies with active involvement from local communities is strongly recommended to ensure the sustainability of these water bodies. J. Sylhet Agril. Univ. 12(2): 127-142, 2025